Velodrom Favorit Brno - Juránek, Marek (Vysoké učení technické v Brně. Fakulta architektury)
Diplomová práce řeší návrh Velodromu-cyklistického stadionu v lokalitě Brno-Komárov, včetně napojení na stávající sportoviště ,parkování a dopravu.

The diploma thesis deals with the design of Velodrom-cycling stadium in the locality Brno-Komárov, including connection to the existing sports ground, parking and transport
Velodrome Favorit Brno
Keywords: Velodrom; dráhová cyklistika; sportoviště; bikros; architektura sportovních staveb; konstrukce; design; Velodrome; track cycling; sports field; cycling; sports buildings architecture; construction; design